The perception of healthcare workers toward primary healthcare communication in South Africa - Sonja Verwey; Andrea Crystal; Tracey Bessin (Communicare)
South Africa's current healthcare conditions show a first world / third world division. The rapid urbanisation of the 1980's and beyond, as well as our population growth rate, has put existing healthcare services under increasing pressure. This Increasing demand, exacerbated by limited funding, necessitates a fundamental restructuring of these services. This means that South African healthcare will have to refocus also from being curative to being more preventative. In such a system communication will have to play a major role as the emphasis clearly would also have to fall on education through the provision of information and guidance. Against this broad background, it would seem that Government has failed to adopt a fully integrated approach to primary healthcare communication. As a result, the allocation of communication resources and the design of communication interventions may not be fully effective in supporting substantive improvements in the primary health status of the country's population. The purpose of this study was to investigate this hypo thesis through a qualitative analysis of the perceptions held by health care workers of the effectiveness and suitability of Governments healthcare campaign